2019
DOI: 10.3390/ijerph16245156
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Trends and Malaria Occurrences in Limpopo Province, South Africa

Abstract: This contribution aims to investigate the influence of monthly total rainfall variations on malaria transmission in the Limpopo Province. For this purpose, monthly total rainfall was interpolated from daily rainfall data from weather stations. Annual and seasonal trends, as well as cross-correlation analyses, were performed on time series of monthly total rainfall and monthly malaria cases in five districts of Limpopo Province for the period of 1998 to 2017. The time series analysis indicated that an average o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…Our results showed that rainfall was positively associated with the risk of being a hotspot, and this nonlinear association depended on vegetation type. While the relationship between rainfall and malaria occurrence has been widely discussed in the literature [15,33,34,46,47], our study indicates that the impact of rainfall on malaria depends on both the amount of rainfall and the type of vegetation, and that this interaction in turn modifies hotspot distribution. Thus, for villages dominated by open shrublands, the risk of being a hotspot increases from the first rains and then reaches a plateau from 22mm/week, likely because heavy rains destroy breeding sites [48,49].…”
Section: Discussionmentioning
confidence: 54%
“…Our results showed that rainfall was positively associated with the risk of being a hotspot, and this nonlinear association depended on vegetation type. While the relationship between rainfall and malaria occurrence has been widely discussed in the literature [15,33,34,46,47], our study indicates that the impact of rainfall on malaria depends on both the amount of rainfall and the type of vegetation, and that this interaction in turn modifies hotspot distribution. Thus, for villages dominated by open shrublands, the risk of being a hotspot increases from the first rains and then reaches a plateau from 22mm/week, likely because heavy rains destroy breeding sites [48,49].…”
Section: Discussionmentioning
confidence: 54%
“…Rainfall was positively associated with the risk of being a hotspot, and this non-linear association depended on vegetation type. While the relationship between rainfall and malaria occurrence has been widely discussed [15,34,35,46,47], our study indicates that the impact of rainfall on malaria occurrence depends on both amount rainfall and vegetation type, and this interaction in turn modifies hotspot distribution. Thus, for villages dominated by open shrublands, the risk of being a hotspot increases from the first rains and then reaches a plateau from 22mm/week, likely because heavy rains destroy breeding sites [48,49].…”
Section: Discussionmentioning
confidence: 61%
“…Our results showed that rainfall was positively associated with the risk of being a hotspot, and this non-linear association depended on vegetation type. While the relationship between rainfall and malaria occurrence has been widely discussed [15,33,34,46,47], our study indicates that the impact of rainfall on malaria occurrence depends on both amount of rainfall and vegetation type, and this interaction in turn modifies hotspot distribution. Thus, for villages dominated by open shrublands, the risk of being a hotspot increases from the first rains and then reaches a plateau from 22mm/week, likely because heavy rains destroy breeding sites [48,49].…”
Section: Discussionmentioning
confidence: 61%